(untitled) (Studia Prawnicze / The Legal Studies, 2014)
Rozstrzyganie konfliktów intertemporalnych nie jest zadaniem prostym. Poniższe opracowanie stanowi próbę skonstruowania koncepcji pozwalającej na w miarę szybkie i prawidłowe rozwiązywanie wątpliwości międzyczasowych, które towarzyszą każdej zmianie stanu prawnego. Autor skoncentrował się wyłącznie na regulacjach należących do prawa zobowiązań. Punktem wyjścia stała się analiza przepisów przechodnich znajdujących się w ustawach nowelizujących Kodeks cywilny oraz w przepisach wprowadzających Kodeks cywilny. Powyższy zabieg ma doprowadzić do odtworzenia schematu, jakim posługuje się sam usta-wodawca przy normowaniu konfl iktów prawa w czasie. It is not an easy task to resolve intertemporal problems. This publication is an attempt to create a theory of solving such concerns, accompanying any changes in legal system, as quickly and correctly. as possible. The author focuses on regulations belonging to the contract law. The starting point of this article was an analysis of transitional provisions contained in amendments to Civil Code and in the introductory regulations of the Civil Code. This procedure leads up to a method of managing intertemporal conflicts between undergone significant changes of the legal system which is used by the legislature itself. Considerations begin with an introduction to the issues of the private intertemporal law by a brief characterization of intertemporal law basic rules approved by literature and jurisdiction. Then, the basic principles of the intertemporal law on the basis of the introductory regulations of the Civil Code have been discussed. At the end of this publication a theory of resolving intertemporal conflicts based on law of contract, which corresponds to the nature of obligations has been indicated.